Analysis of User Satisfaction Level of Ajaib Kripto Application in DKI Jakarta - Amar Bastian (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This research aims to determine the level of satisfaction of users of the Ajaib Crypto application in DKI Jakarta. The sample used in this research was 120 respondents with the criteria of living in DKI Jakarta, and active users of the Ajaib Crypto application for at least three months. This research uses three dimensions, namely ease of use, information and system settings and usability. The results of this research show that the level of satisfaction of users of the Ajaib Crypto application in DKI Jakarta is in the Very Satisfied category. Based on the t test, there is no significant difference between the three dimensions and based on the average calculation, there is one attribute that needs to be improved, namely application performance.